Generational Perspectives on Community Knowledge Transfer in Nipissing First Nation - Blenkinsop, Lisa M. (University of Guelph, 2017)
Indigenous knowledge is the living knowledge held by a particular community that is shared with, and transformed by, each successive generation. This thesis explores historical and contemporary intergenerational knowledge transfer at Nipissing First Nation, an Anishinaabe community in Ontario, Canada, that is working to restore its community knowledge and worldview while also dealing with conflict surrounding its commercial fisheries. Elders and youth from the community were invited to participate in a community-led workshop aimed at connecting generations and creating a space for knowledge-sharing and dialogue. Drawing on the workshop discussions I explored themes that emerged, including the disruption of historical mechanisms of intergenerational knowledge transfer in the community as a direct consequence of colonization and the imposition of the Western worldview onto the community. This disruption of intergenerational knowledge transfer has disconnected contemporary children and youth from traditional relationships with the land, the Anishinaabe language, the community and their Elders. Social Sciences and Humanities Research Council of Canada